2022
DOI: 10.31602/zmip.v47i2.7136
|View full text |Cite
|
Sign up to set email alerts
|

Evaluasi Kandungan Mutu Fisik Dan Kimia Susu Sapi Perah Friesian Holstein Di Bppib TSP Bunikasih

Abstract: Fresh milk that is good for consumption in terms of nutritional content and food safety must meet the applicable SNI. The quality of milk is largely determined by the components of substances contained in milk, including knowing the physical quality and chemical nutrient content. Research on Evaluation of Physical and Chemical Quality Content of Friesian Holstein Dairy Cows at BPPIB TSP Bunikasih was carried out in April-May 2021. The purpose of this study was to determine the physical quality of milk (color, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The color seen by the panelists in the functional food product kefir is because the basic ingredient in making kefir is cow's milk which is yellowish white in color. This is supported by Christi et al (2022) [2] reported that the color of milk is bluish white and golden yellow which is caused by fat globules, while the blue color of milk is caused by the protein content being higher than the fat content. The fat in milk will be degraded by lactic acid bacteria which produces a yellowish white kefir color.…”
Section: Discussionmentioning
confidence: 63%
“…The color seen by the panelists in the functional food product kefir is because the basic ingredient in making kefir is cow's milk which is yellowish white in color. This is supported by Christi et al (2022) [2] reported that the color of milk is bluish white and golden yellow which is caused by fat globules, while the blue color of milk is caused by the protein content being higher than the fat content. The fat in milk will be degraded by lactic acid bacteria which produces a yellowish white kefir color.…”
Section: Discussionmentioning
confidence: 63%
“…The main ingredient in milk caramel candy is pure cow's milk. Pure cow's milk is produced from secretory cells in cows' udder through the nipples with white liquid, complete nutritional components, and is suitable for body health (Christi et al, 2022).…”
Section: Introductionmentioning
confidence: 99%